Valores de hemoglobina, hierro sérico y riesgo de anemia en niños del I.E. Virgen del Carmen Alto Trujillo, Enero 2019 - Zavaleta Ventura, Lucy Victoria (2019)
The objective of the work was to determine the hemoglobin, serum iron and the risk of anemia in the children of the Educational Institution Virgen del Carmen district El Porvenir, January 2019, 60 blood samples were used from 32 children and 28 girls between 8-11 years. Prior to informed consent and participation consent for inclusion in the study. The anthropometric measurements were made using the following variables: weight (Kg) and height (cm) and biochemical indicators: determination of Hb (Cyanomethaemoglobin method), hematocrit (Microcentrifugation), serum iron and thus determine the risk of anemia in children School age. The average values were Hemoglobin (Hb) 12.2 g / dl ± 0.74, Hematocrit (Hto) 37.68% ± 1.98 and serum iron 87.11 ug / dl ± 28.96. The 16.67% of children presented decreased hemoglobin values, this percentage according to the BMI, represented 8.33% with low weight and 8.33% with normal weight. According to the age group, the group of 7-8 years represented 5% and the group of 9-10 years represented 11.67%. And according to sex, 10% of women and 6.67% of men. The 13.33% of children presented diminished serum iron values, this percentage according to the BMI, represented 8.33% with low weight, and 5% with normal weight. According to the age group, the group of 7-8 years represented 3.33%, and of the group of 9-10 years, 10% and according to sex, 8.33% of females and 5% of males. It was concluded that 13.33% have hemoglobin, hematocrit and decreased serum iron, which indicates a risk of anemia